Dopant-induced property modifications in aqueous-synthesized SiC nanoparticles - Esmael, M. M.; Omar, M. S.; Degdelen, F. (Academic Press Ltd- Elsevier Science Ltd, 2026)
In this study, aluminum (Al), vanadium (V), and nitrogen (N) doped silicon carbide (SiC) nanoparticles were successfully synthesized using pulsed laser ablation in water (PLAL), a green and surfactant-free method. Doping was used to enhance the optical and structural properties of SiC nanoparticles. Ultraviolet-visible spectroscopy confirmed that N, Al, and V doping systematically narrowed the optical energy gap of SiC nanoparticles from 3.2 eV (undoped) to 2.37-3.11 eV, depending on the dopant type and concentration. Fourier transform infrared spectroscopy confirmed the preservation of Si-C bonds and revealed dopant-specific vibrational features, while the absence of secondary oxide or nitride phases indicated clean substitutional doping. Field-emission scanning electron microscopy showed that Al-doped (similar to 15 nm) and N-doped (similar to 14 nm) particles exhibited reduced size and enhanced crystallinity. In contrast, V-doping yielded larger (similar to 30 nm) particles with deep-level defects. Energy-dispersive X-ray spectroscopy confirmed successful incorporation of Al, N, and V, with dopant-specific peaks and variations in the Si:C ratio, indicating substitutional doping and defect-complex formation. Hall-effect measurements confirmed the semiconducting behavior of SiC nanoparticles, showing that conductivity increased with temperature (300-500 K) while mobility decreased due to phonon scattering. Doping enhanced conductivity but reduced mobility through impurity scattering, with Al-and N-doped SiC exhibiting the most favorable balance. After standardizing the particle size at 8 nm to remove size effects, Eg decreased from 3.2 eV (undoped) to 2.41 eV (N-SiC), 2.48 eV (Al-SiC), and 2.8 eV (V-SiC). The reduction indicates that dopants introduce localized states within the band gap, with nitrogen producing the most substantial effect. These results confirm that doping effectively tailors the electronic structure of SiC nanoparticles.
Keywords: Silicon carbide; Nanocomposite; Laser ablation in liquid; Doping; Band gap engineering; Hall effect